Prognostic value of the expression and localization of cell proliferation and apoptosis markers in unicystic ameloblastomas - Rebeca Vieira Costa; Karolyny Martins Balbinot; Gabriela Cristina Avertano Rocha da Silveira; Maria Sueli da Silva Kataoka; Silvio Augusto Fernandes de Menezes; Vanessa Morais Freitas; Ana Carolina Uchoa Vasconcelos; Adriana Etges; Victor Angelo Martins Montalli; Fabricio Passador Santos; Sérgio de Melo Alves Júnior; Ruy Gastaldoni Jaeger; et al. (Scientific Reports, 2024)
Abstract The aim of this study was to verify whether the expression of cell proliferation and apoptosis markers in different types of unicystic ameloblastoma (UA) is associated with the location of neoplastic cells. Immunohistochemical study with a sample of 32 cases of UA, 11 cases of conventional ameloblastoma (CAM) and ten dental follicles (DF) cases was performed. Cell proliferation was assessed using Ki-67 status, and apoptosis by caspase-3 expression. Mural UA (MUA) showed a higher immunostaining of Ki-67 (p < 0.05) and a lower immunostaining of Caspase-3 (p < 0.05) compared with luminal and intraluminal subtypes of UA and CAM. The neoplastic cells of the MUA’s cystic capsule showed a higher expression of Ki-67 protein (p < 0.0001) and a lower expression of Caspase-3 (p < 0.0001) compared with the lumen. DF showed lower Ki-67 and Caspase-3 immunostaining (p < 0.05) than neoplasms. The higher immunoexpression of Ki-67 and the lower immunoexpression of Caspase-3 in MUA, in the parenchyma cells within the cystic capsule, suggest an association between the biological behaviour and location of neoplastic cells in a tumour.